2022
DOI: 10.1038/s41598-022-05830-7
|View full text |Cite
|
Sign up to set email alerts
|

Trap-state mapping to model GaN transistors dynamic performance

Abstract: Trapping phenomena degrade the dynamic performance of wide-bandgap transistors. However, the identification of the related traps is challenging, especially in presence of non-ideal defects. In this paper, we propose a novel methodology (trap-state mapping) to extract trap parameters, based on the mathematical study of stretched exponential recovery kinetics. To demonstrate the effectiveness of the approach, we use it to identify the properties of traps in AlGaN/GaN transistors, submitted to hot-electron stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…These data also manifest a UV/visible rejection ratio of about 5.1 × 10 3 at a bias voltage of 100 mV. Compared to the PDCR of 7.0 × 10 4 at 100 mV, the difference between these two ratios may be originated from the trap states , related to material defects , or inevitably created during the RIE-ICP processes . Nevertheless, this ratio under low voltage still outperforms the traditional GaN Schottky photodetectors which require to operate at a much higher voltage. …”
Section: Resultsmentioning
confidence: 83%
“…These data also manifest a UV/visible rejection ratio of about 5.1 × 10 3 at a bias voltage of 100 mV. Compared to the PDCR of 7.0 × 10 4 at 100 mV, the difference between these two ratios may be originated from the trap states , related to material defects , or inevitably created during the RIE-ICP processes . Nevertheless, this ratio under low voltage still outperforms the traditional GaN Schottky photodetectors which require to operate at a much higher voltage. …”
Section: Resultsmentioning
confidence: 83%
“…Some studies report the interface/surface trapping to dominate in the hard turn-ON process while observing the impact of buffer region design [66], [67] and drain field plate design [71] on surface trapping. Studies have also shown that the traps relevant to the hard turn-ON process possess a broadly-distributed but relatively shallow energy level [72], [73].…”
Section: A Dynamic On-resistancementioning
confidence: 99%
“…The full discussion of the methodology used in this article to extract the time constant distribution of the deep levels of interest can be found in [25]. Here, we provide a brief summary; considering (1), A i and τ i are the parameters of the single exponential components constituting the multiexponential threshold voltage transient.…”
Section: Trap Properties Extractionmentioning
confidence: 99%
“…4 shows the contour map of the time constant distribution (decay rate probability density function [26]) at different temperatures extracted from the experimentally measured V TH recovery transients in Fig. 3 following the procedure presented in [25]. It is important to stress that the extracted time constant distribution of f (t) does not have a Gaussian shape and differs from the simple derivative of the transient d f (t)/dlog(t) [27], which has no direct meaning in relation to trap properties.…”
Section: Trap Properties Extractionmentioning
confidence: 99%
See 1 more Smart Citation